A DGFEM for nondivergence form elliptic equations with Cordes coefficients on curved domains. Issue 5 (1st April 2019) - Kawecki, Ellya L.
Abstract : I. Smears and E. Süli designed and analyzed a discontinuous Galerkin finite element method for the approximation of solutions to elliptic partial differential equations in nondivergence form. The results were proven, based on the assumption that the computational domain was convex and polytopal . In this paper, we extend this framework, allowing for Lipschitz continuous domains with piecewise curved boundaries.